Multistability and predominant hybrid phenotypes in a four node mutually repressive network of Th1/Th2/Th17/Treg differentiation - Atchuta Srinivas Duddu; Elizabeth Andreas; Harshavardhan BV; Kaushal Grover; Vivek Raj Singh; Kishore Hari; Siddharth Jhunjhunwala; Breschine Cummins; Tomas Gedeon; Mohit Kumar Jolly (npj Systems Biology and Applications, 2024)
Abstract Elucidating the emergent dynamics of cellular differentiation networks is crucial to understanding cell-fate decisions. Toggle switch – a network of mutually repressive lineage-specific transcription factors A and B – enables two phenotypes from a common progenitor: (high A, low B) and (low A, high B). However, the dynamics of networks enabling differentiation of more than two phenotypes from a progenitor cell has not been well-studied. Here, we investigate the dynamics of a four-node network A, B, C, and D inhibiting each other, forming a toggle tetrahedron. Our simulations show that this network is multistable and predominantly allows for the co-existence of six hybrid phenotypes where two of the nodes are expressed relatively high as compared to the remaining two, for instance (high A, high B, low C, low D). Finally, we apply our results to understand naïve CD4+ T cell differentiation into Th1, Th2, Th17 and Treg subsets, suggesting Th1/Th2/Th17/Treg decision-making to be a two-step process.